Qualitative Phytochemical Analysis of Gracilaria verrucosa from North Sulawesi Waters - Luringunusa, Ekklesia; Sanger, Grace; Sumilat, Deiske A.; Montolalu, Roike Iwan; Damongilala, Lena J.; Dotulong, Verly (Sam Ratulangi University, 2023)
The research aims to determine the phytochemical content such as phenolics, flavonoids, tannins, saponins, alkaloids, steroids, and triterpenoids found in the seaweed G. verrucosa. Seaweed G. verrucosa taken from the waters of North Sulawesi, Nain Village, North Minahasa, was extracted by maceration for 24 hours at room temperature, repeated 3 times using 96% ethanol solvent. The analysis in this study consisted of seven test parameters such as phenolic compounds, flavonoids, tannins, saponins, steroids, triterpenoids, and alkaloids. The results of the analysis showed that the secondary metabolites of G. verrucosa contained phytochemical compounds such as phenols, flavonoids, tannins, saponins, steroids, and alkaloids, and no triterpenoid compounds were found. It was concluded that G. verrucosa which grows in the waters of North Sulawesi, Nain Village, can function as functional food, and medicine because it has natural bioactive compounds. Keywords: Phytochemical content, Gracilaria verrucosa, secondary metabolites Abstrak Penelitian bertujuan mengetahui kandungan fitokimia seperti fenol, flavanoid, tanin, saponin, alkaloid, steroid, dan triterpenoid yang terdapat pada rumput laut G. verrucosa. Senyawa metabolit sekunder yang umum terdapat pada tanaman adalah senyawa terpenoid, alkaloid, fenolik, streroid, saponin, tannin. Rumput laut G. verrucosa yang di ambil dari perairan Sulawesi Utara Desa Nain Minahasa Utara di ekstraksi dengan cara maserasi selama 24 jam pada suhu ruang di ulangi sebanyak 3 kali menggunakan pelarut etanol 96 %. Analisis pada penelitian ini terdiri dari tujuh parameter pengujian seperti senyawa fenol, flavonoid, tanin, saponin, steroid, triterpenoid dan alkaloid. Hasil analisis menunjukan bahwa kandungan metabolit sekunder dari G. verrucosa mengandung senyawa fitokimia seperti fenol, flavonoid, tanin, saponin, steroid, alkaloid dan tidak ditemukan adanya senyawa triterpenoid. Hal ini disimpulkan bahwa G. verrucosa yang tumbuh di perairan Sulawesi utara Desa Nain dapat berfungsi sebagai pangan fungsional, obat-obatan karena memiliki senyawa bioaktif alami. Kata kunci: Kandungan fitokimia, Gracilaria verrucosa, metabolit sekunder